Development of Music in Indonesia - Sukotjo Sukotjo (Institut Seni Indonesia Denpasar, 2024)
Purpose: This article aims to discuss the problems that occur in the music industry in Indonesia, namely in the order of production, reproduction and marketing. Methods: This article uses a literature study method obtained from various sources. Results and discussion: production, reproduction and marketing arrangements must be handled professionally to establish harmony within the music industry network in Indonesia. Competition from several music industry players in the world does not prevent Indonesia from looking for formats to develop its music industry. The strengths that exist between government, academics, business and community are sectors that must be strengthened in developing the music industry in Indonesia. Implication: development of the music industry in Indonesia from upstream to downstream so that large areas of Indonesia can be reached in the music industry. Apart from that, we should also pay attention to some of the potential of music that exists in several regions in Indonesia which can be used as a mainstay in developing a music industry that is unique to the Indonesian nation.